Chalcone and Curcumin Derivatives: A Way Ahead for Malarial Treatment - Kumar, Dileep; Kumar, Manish; Kumar, Ashok; Kumar Singh, Sushil (Mini Reviews in Medicinal Chemistry, 2013)
Malaria has been a major cause of morbidity and mortality in developing countries, particularly in Sub-Saharan Africa and South Asia. The global malaria situation is increasingly being challenging owing to lack of credible malaria vaccine and the emergence of drug resistance to most of the available antimalarials. They demand search for novel generation of drugs. Versatility and flexibility for structural modification of natural and synthetic analogues of curcumin and chalcone have been explored extensively for designing new antimalarial agent. Recent advances to our knowledge of parasite biology as well as the availability of the genome sequence, have opened up new vista in the firmament of antimalarial drug designing for identifying novel molecular targets. Curcumin and chalcones has been reported to exert anti-malarial effect by binding directly to numerous signaling molecules, such as histone acetyltransferase, histone deacetylase, sarco (endo) plasmic reticulum Ca2+-ATPase, cysteine proteases etc. This review highlights insights the more recent antimalarial activities of these compounds, their mechanisms of action, molecular targets and relevant structureactivity relationship studies. Natural lead compounds like chalcone and curcumin have shown good and optimal binding to many enzymes present in parasite and can be explored as molecular targets for in silico studies to develop new, affordable and effective antimalarial drugs. With no credible malaria vaccine in sight, there is an imperative need to develop new drugs with different mechanisms of action to help preclude issues of cross-resistance.
Keywords: Molecular Targets